Neural Correlates of Preference: A Transmodal Validation Study - Akiba, Henrique T.; Costa, Marcelo F.; Gomes, July S.; Oda, Eduardo; Simurro, Paula B.; Dias, Alvaro M. (Frontiers in Human Neuroscience, 2019)
Liking is one of the most important psychological process associated to the reward system, being involved on affective processing and pleasure/displeasure encoding. Affective reactions can be described in terms of two fundamental dimensions: valence (pleasure/displeasure) and arousal (activation/inhibition). These dimensions have declarative and non-declarative constituents and a vast number of studies have put efforts to build bridges among them, nevertheless, it is still not clear what is the combination of physiological indicators which best describe the neurobiological, especially when applied to dynamic and complex stimuli such as videos. We believe that one of the main problems is the lack of a standard methodology which takes into account the narrative and semantic aspects of the stimulus, therefore we developed a time-dependent method to evaluate the physiological correlates (through electroencephalogram, electrocardiogram and eye tracking) of the likeability for three different categories, namely: adventure, comedy and landscape. Twenty-eight healthy adults with ages between 18 to 35 years (mean age: 23.85 years) were enrolled on the study, the participants asked to provide likeability ratings to videos as they watched them using a response box. Three 60 seconds videos were presented, one for each thematic category, on randomized order on a LCD screen while their physiological data was recorded. Univariate analysis showed significant differences between videos for all the subjective measure variables and significant differences between the physiological patterns preceding the moments of maximum and the minimum ratings in more than 75% of electroencephalogram derived variables, significant differences for phasic cardiac response on comedy and adventure and significant differences for pupil size on comedy and landscape video. Multiple linear regressions were conducted predicting the likeability on each video using physiological variables; all models were significant (p<0.05) and explained over 30% of variability over chance (adj. R2>0.30). The instant which maximizes the prediction was calculated as well. In this sense, the employment of time-dependent techniques to assess subjective liking and its physiological correlates allows for more precise and informative assessment of the psychophysiological reactions induced by videos than the traditional global evaluation approach.